Home-based exercise program integrated with patient education for patients with type 2 diabetes mellitus: a study on feasibility and preliminary effectiveness - Mustapa, Nurul Amirah; Justine, Maria; Manaf, Haidzir (2023)
Background: Exercise has been considered one of the cornerstones in managing type 2 diabetes mellitus (T2DM). However, it is known as an underutilized approach in clinical practice. Considering the hectic schedule of healthcare providers in educating exercise for this population, we developed a home-based exercise program for T2DM patients to promote exercise involvement. Methods: A 3-phased study was conducted. Phase 1 was the development of the program involved systematic reviews to identify the exercise protocol and health belief model (HBM)-based education on exercise behavior. Phase 2 consisted of content validation of the program. In phase 3, T2DM patients were recruited to enroll in four 60-min education sessions. Two weekly supervised resistance exercise sessions for four weeks were followed by eight weeks of home-based resistance exercise. Simultaneously, the participants performed home-based aerobic exercises for 12 weeks. Process and scientific feasibility were analyzed for feasibility. Results: Of 15 participants who consented to partake, 11 participants completed the intervention (73%). The prescribed intensity of aerobic and resistance exercise was achieved by 46% and 82% of the participants, respectively. Adherence rates to home-based exercises ranged from 60% to 64%. No study-related severe adverse event was reported. Mean glycated hemoglobin (HbA1c) decreased from 7.9% to 7.7%, the six-minute walk test (6MWT) increased from 404.1 m to 465.4 m, muscle strength (handheld dynamometer) increased from 6.2 kg to 7.6 kg (elbow flexor); from 6.5 kg to 7.8 kg (knee extensor), muscle mass increased from 23.6% to 23.8%, and fat mass decreased from 35.6% to 35.2%. The participants showed improvement in exercise self-efficacy (ESE) (from 44.8 to 66.6) and Quality of Life (QoL) (from 45.7% to 32.4%). Conclusion: The program had a potentially positive outcome on glycemic control, aerobic capacity, muscle strength, body composition, ESE, and QoL in T2DM patients.